Effect of CYP2C19 and CYP2D6 genotype on tamoxifen treatment outcome indicates endogenous and exogenous interplay. (19th July 2018) - Sim, Sarah; Lövrot, John; Lindh, Jonatan D; Bergh, Jonas; Xie, Hanjing
Aim: We investigated the interaction of CYP2C19 and CYP2D6 genotype on clinical outcome in tamoxifen-treated breast cancer patients.Materials & methods: A cohort of 306 patients on tamoxifen treatment for a minimum of 1 year were employed to analyze the effect of genotype-predicted phenotype on relapse-free survival.Results & conclusion: We show that the group with worst outcome and highest risk of relapse is that of 2C19↑–2D6↓ (hazard ratio: 2.94), when adjusting for age, Nottingham prognostic index and adjuvant chemotherapy. Furthermore, the effect of 2C19↑–2D6↓genotype-predicted phenotype is greatly enhanced in premenopausal patients (hazard ratio: 21.08). We hypothesize that poor bioactivation of tamoxifen in patients with low CYP2D6 activity and high CYP2C19 metabolism represents a tamoxifen-treated patient group that has the worst clinical outcome.